Keanekaragaman, aktivitas kunjungan, dan keefektifan lebah penyerbuk pada tanaman tomat (Solanum lycopersicum L: Solanaceae) - Andi Gita Maulidyah Indraswari; Tri Atmowidi; Sih Kahono (Jurnal Entomologi Indonesia, 2016)
Tomato (Solanum lycopersicum L.) is a hermaphrodite plant and capable of auto pollination. However it still need pollinators to maximize pollination success. This research was aimed to determine the diversity, foraging activity of pollinator bees and its effectiveness on seeds and fruits formation of tomato. Scan sampling method was used to determine the diversity of pollinators and focal sampling method was used to observe visiting behavior of the bees. We conducted two experiments i.e., screen caged plants and open plants to compare the effect of the bee pollinators on fruits and seeds set formation. Results showed that eleven species of bees were found, i.e., Megachile conjuncta Smith, Megachile fulfifrons Smith, Megachile unbripennis Smith, Xylocopa confusa Latreille, Xylocopa latipes Drury, Xylocopa caerulea Fabricius, Ceratina cognata Latreille, Nomia quadridentata Bingham, Amegilla cyrtandrae Lieftinck, Amegilla burneensis Friese, and Apis cerana Fabricius. Three species of bees were dominant, i.e., X. confusa, A. cyrtandrae, and C. cognata. Bee, X. confusa visited more flowers per minute, followed by A. cyrtandrae and C. cognata. The longest species visiting in plants were C. cognata, followed by X. confusa and A. cyrtandrae. Bee pollinators increase 8.92% of fruiting, 43% of fruit size, 189% of number of seeds per fruit, and 355% of weight of seeds of tomato plants.